2015
DOI: 10.17221/8556-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Carcass composition and meat quality of Czech genetic resources of nutrias (Myocastor coypus)

Abstract: ABSTRACT:The effects of sex and colour type on carcass composition, nutrients content, and muscle fibre characteristics of hind leg meat of nutrias raised under intensive conditions were the focus of this study. Thirtysix eight-month-old nutrias of both sexes with three colour types (Standard nutria, ST; Moravian Silver, MS; and Prestice Multicolour, PM) were studied. Live weight was affected by colour type (P < 0.05) and sex (P < 0.001); however, no effects of these variables were found for the dressing out p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…Feed intake was higher in males. Dressing out percentage was not affected by the colour type or sex, Tůmová et al (2015) reported higher values in males. The hind leg meat weight was affected by the interaction of colour type and sex (P≤0.009) with the highest weight in males MS and PV (544 g) and the lowest in females MS (301 g).…”
Section: Detailed Abstractmentioning
confidence: 72%
See 1 more Smart Citation
“…Feed intake was higher in males. Dressing out percentage was not affected by the colour type or sex, Tůmová et al (2015) reported higher values in males. The hind leg meat weight was affected by the interaction of colour type and sex (P≤0.009) with the highest weight in males MS and PV (544 g) and the lowest in females MS (301 g).…”
Section: Detailed Abstractmentioning
confidence: 72%
“…U jednotlivých partií jatečně opracovaného trupu jsou v literatuře dostupné pouze podíly, nikoli však hmotnosti. Podíl zadní části a stehen byl vyšší u samic (Tůmová et al, 2015). Podobně jako u předchozích ukazatelů tak i podíl masa stehen byl vyšší u samic (Tůmová a Hrstka, 2013).…”
Section: úVodunclassified
“…Relationship between age and body weight in nutria (Myocastor coypus) males and females maintained either on an extensive (ERF) or intensive (IFR) feeding regime (lower figure represents longer time window). Grey data points without border represent literature data on intensively reared animals (Niedźwiadek et al, 1987a;Niedźwiadek and Piórkowska, 1993;Sirotkin et al, 2003;Cabrera et al, 2007;Beutling et al, 2008;Tůmová et al, 2015;Tůmová et al, 2017), the black and dotted lines represent growth curves for free-ranging males and females, respectively (Dixon et al, 1979), the small black symbols represent free-ranging animals from Sherfy et al (2006), and the crosses represent free-ranging animals of unknown sex from Peloquin (1969) in which an increase in body weight in the spring (1 yr after birth) from the extensive feeding regime (EFR) level to the intensive feeding regime (IFR) level is visible. production, but for general concepts on the determinate growth of endotherms.…”
Section: Discussionmentioning
confidence: 99%
“…For comparative purposes, data on age and BW were plotted against literature data on nutria from the wild (Peloquin, 1969;Dixon et al, 1979;Willner et al, 1980;Sherfy et al, 2006) and intensive rearing systems (Niedźwiadek et al, 1987a;Niedźwiadek and Piórkowska, 1993;Sirotkin et al, 2003;Cabrera et al, 2007;Beutling et al, 2008;Tůmová et al, 2015;Tůmová et al, 2017).…”
Section: Statistical Analysis and Interpretationmentioning
confidence: 99%